Current state of seagrass ecosystem services: Research and policy integration. (15th November 2017) - Ruiz-Frau, A.; Gelcich, S.; Hendriks, I.E.; Duarte, C.M.; Marbà, N.
Abstract: Seagrasses contribute to the maintenance of human wellbeing. However certain aspects of their role as ecosystem service (ES) providers remain understudied. Here, we synthesise the state of seagrass ES (SGES) research and policy implications. Additionally, we recommend ways in which SGES research can be integrated in to policy design, by drawing lessons from the case of Blue Carbon (BC). SGES research suffers from three main biases: a geographical bias, SGES has been restricted to chartered seagrass areas; a type of service research bias, provisioning and regulating services have received extensive attention while cultural services remain understudied; a type of discipline bias, the ecological aspects of SGES have been well documented while economic and social aspects remain in comparison understudied. These are particularly important, as an understanding of the social and economic considerations of the provision of ES is fundamental to facilitate its integration into policy frameworks. Lessons drawn from the operationalization process of BC show the reoccurrence of certain aspects that have enabled the integration of BC into policy. These aspects are grouped under 4 different categories. From the analysis of these elements we draw lessons that could facilitate the operationalization of other ecosystem services and their incorporation into management policy frameworks. Highlights: Seagrass ecosystem services (SGES) research suffers from three main research biases. Geographical bias: research has been mostly limited to chartered areas. Service type bias: cultural services remain understudied. Discipline bias: economic and social aspects of SES need more attention. The operationalization of SGES will need the fulfilment of these three knowledge gaps.